2018
DOI: 10.1158/1535-7163.mct-17-1273
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MEK in a Translational Model of Histiocytic Sarcoma

Abstract: Histiocytic sarcoma in humans is an aggressive orphan disease with a poor prognosis as treatment options are limited. Dogs are the only species that spontaneously develops histiocytic sarcoma with an appreciable frequency, and may have value as a translational model system. In the current study, high-throughput drug screening utilizing histiocytic sarcoma cells isolated from canine neoplasms identified these cells as particularly sensitive to a MEK inhibitor, trametinib. One of the canine cell lines carries a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 75 publications
0
24
2
2
Order By: Relevance
“…Prolonged mitotic block results in apoptosis induction and eventual cell death [62,63]. In a similar way, inhibition of MEK1/2 with trametinib induced death of various tumor cells that are heavily dependent on elevated RAS-RAF-MEK1/2-ERK1/2 cascade activity [64][65][66][67]. In contrast to these reports, we did not detect any cytotoxic effects caused by MEK1/2 inhibition in HGSOC cells.…”
Section: Trametinib Treatment Drastically Reduces the Growth Rates Ofcontrasting
confidence: 53%
“…Prolonged mitotic block results in apoptosis induction and eventual cell death [62,63]. In a similar way, inhibition of MEK1/2 with trametinib induced death of various tumor cells that are heavily dependent on elevated RAS-RAF-MEK1/2-ERK1/2 cascade activity [64][65][66][67]. In contrast to these reports, we did not detect any cytotoxic effects caused by MEK1/2 inhibition in HGSOC cells.…”
Section: Trametinib Treatment Drastically Reduces the Growth Rates Ofcontrasting
confidence: 53%
“…In the future, this test could be considered in veterinary oncology, to guide treatment procedure toward targeted therapy. Indeed, others and us showed that PTPN11 mutations were associated with the activation of the MAPK pathway, and in vitro test showed that canine HS cell lines were sensitive to MEK inhibitors 27,59,60 . As our ctDNA assay demonstrated a sensitivity of 91.3% and a specificity of 100% for the detection of PTPN11 mutation in the plasma of dogs carrying PTPN11 mutated HS, it could efficiently select dogs susceptible to benefit from this targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream to SHP-2, MAPK and PI3K/AKT pathways are also potential targets for neoplasms with mutated PTPN11 and KRAS , and for which several FDA-approved inhibitors are currently available. We have demonstrated that trametinib, an MEK inhibitor, significantly inhibited canine HS cells by promoting cell cycle arrest and cell apoptosis [32]. Additionally, trametinib prolonged survival of mice carrying xenograft HS orthotopically (intrasplenic) [33,46].…”
Section: Discussionmentioning
confidence: 99%
“…HS cell lines derived by our laboratory from BMDs (BD and OD), a Rottweiler (PJ) and a golden retriever (DH82, obtained from ATCC (CRL-10389)) were also included in the study. A comprehensive characterization of the BD, OD and PJ cell lines has been reported by our group [32,35]. DH82 is a commercially available cell line reportedly derived from a hemophagocytic HS in a golden retriever.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation